American gangster - Grazer, Brian, 1953-; Scott, Ridley; Zaillian, Steven; Washington, Denzel, 1954-; Crowe, Russell, 1964-; Ejiofor, Chiwetel, 1974-; Brolin, Josh.; Nadal, Lymari; Dee, Ruby; Levine, Ted.; Smith, Roger Guenveur; Hawkes, John, 1959-; et al. (Universal City, Calif. : Universal Studios Home Entertainment, 2008)
Following the death of his employer and mentor, Bumpy Johnson, Frank Lucas establishes himself as the number one importer of heroin in Harlem, buying heroin directly from a source in South East Asia. His alliance with the New York Mafia ensures his position. Richie Roberts is a dedicated and honest policeman who heads up a joint narcotics task force with the Federal government. Based on a true story.
Disc 1. English and French tracks: Dolby digital 5.1. Disc 2. English track: Dolby digital 2.0.
Title from container.
Based on the article "The return of Superfly" by Mark Jacobson.
Originally released as a motion picture in 2007.
Special features: Disc 1: unrated extended version; commentary with director Ridley Scott and writer Steven Zailian. Disc 2: Deleted scenes including an alternate opening; 'Fallen empire : making American gangster'; case files.
Director of photography, Harris Savides ; editor, Pietro Scalia ; music, Marc Streitenfeld ; costume designer, Janty Yates ; production designer, Arthur Max.
Keywords: Lucas, Frank, -- 1930- -- Drama; Heroin industry -- Drama; Drug traffic -- New York (State) -- New York -- Drama; Gangsters -- New York (State) -- New York -- Drama; Detectives -- New York (State) -- New York -- Drama; Criminal behavior -- New York (State) -- New York -- Drama; Harlem (New York, N.Y.) -- Drama; Gangster films; Thrillers (Motion pictures, television, etc.); Video recordings for the hearing impaired; Feature films; Suspense films